2020
DOI: 10.1101/2020.03.11.20030957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical features and outcomes of 2019 novel coronavirus–infected patients with cardiac injury

Abstract: Aims To explore the epidemiological and clinical features of 2019 novel coronavirus(2019-nCoV)-infected patients with cardiac injury . Methods and results Data were collected from patients medical records, and we defined cardiac injury according to cardiac biomarker troponin I level > 0.03>ug/L. Among the 291 patients, 15 (5.2%) showed evidence of cardiac injury. Of 16 hospitalized patients with cardiac injury, the median age was 62 years, and 11/15 (73.3%) were men. Underlying cardiovascular diseases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
(7 reference statements)
1
22
0
Order By: Relevance
“…Additionally, we found in our normalized dataset that heart tissues also had the third highest level of ACE2 expression. This observation is also in line with reports showing that COVID-19 patients complicated with cardiac diseases are subject to the highest mortality risk 40,41 . Together, the consistence between our results and clinical observations demonstrated that ACE2 expression is a reasonable indicator for susceptibility to SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we found in our normalized dataset that heart tissues also had the third highest level of ACE2 expression. This observation is also in line with reports showing that COVID-19 patients complicated with cardiac diseases are subject to the highest mortality risk 40,41 . Together, the consistence between our results and clinical observations demonstrated that ACE2 expression is a reasonable indicator for susceptibility to SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 92%
“…The increased incidence of cardiac injury among those with severe systemic inflammatory response syndromes (SIRS) and shock in the setting of COVID-19 also highlights an important relationship between the immune response to the virus and the cardiovascular system. In addition, a high prevalence of pre-existing cardio-metabolic disease has been noted among those with severe COVID-19 [16,17], and those with pre-existing cardiovascular conditions suffer increased mortality during COVID-19 infection [18]. In particular, the reported case fatality rates for COVID-19 are 10.5% in patients with cardiovascular disease, 7.3% in patients with diabetes, and 6.0% in those with hypertension, higher than the case-fatality rate of 3-4% observed world-wide for patients without these co-morbidities [7••].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of CRRT use to ICU admissions was 19.7%. The four unpublished reports included 593 patients, with 151 patients requiring ICU admission and 36 receiving CRRT ( 14 17 ). Among all the included patients with COVID-19, about 20% of the patients who had acute respiratory distress syndrome or needed ICU admission received CRRT.…”
Section: Resultsmentioning
confidence: 99%